Islamic Religious Education Students’ Perceptions of the Origin of Humans, the Creation of the Universe, and the Shape of the Earth from the Perspective of Science and Islam - Harosid, Harun (Scientica Education Journal, 2025)
This study aims to describe the perceptions of Islamic Religious Education (PAI) students on three main issues that are the subject of debate between science and religion: the origins of humans, the creation of the universe, and the shape of the earth. Using a quantitative method with a descriptive approach, this study involved 70 new students of the PAI Study Program at KH. Ruhiat Cipasung Islamic University, Tasikmalaya Regency, who were selected purposively. The instrument used was a closed-ended Likert-scale questionnaire, with descriptive statistics as the data analysis technique. The results showed that all respondents believed that Prophet Adam was the first human, although 12.9% of them were open to the possibility of integration with the theory of evolution. As many as 75.7% stated that the Big Bang theory does not contradict the concept of creation in the Qur'an, while 90% believed the shape of the earth is spherical, in accordance with a non-literal interpretation of the verses of the Qur'an. These findings indicate an integrative and moderate tendency among PAI students in addressing the differences between science and Islam. This study has important implications for the development of an PAI curriculum that can bridge science and religion critically and harmoniously.